A Stall Metric to Track Communication Performance - Mink, Alan; Salamon, Wayne; lndovina, Michael (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1999)
Probing the communication protocol stack in Linux PC-based clusters to investigate erratic TCP/IP performance has led to a new metric, data stream stall, which is analogous to instruction stream stall in CPUs. Data stream stalling correlates well with unexpected throughput performance dips; the dips are usually due to delayed ACKs or questionable handling of them. We illustrate the use of this data stream stall metric by isolating and correcting the cause of these communication throughput dips in our version of Linux (2.0.29). The availability of this data stream stall metric would provide useful feedback to users by indicating deficient communications performance.Probing the communication protocol stack in Linux PCbased clusters to investigate erratic TCP/IP performance has led to a new metric, data stream stall, which is analogous to instruction stream stall in CPUs. Data stream stalling correlates well with unexpected throughput performance dips; the dips are usually due to delayed ACKs or questionable handling of them. We illustrate the use of this data stream stall metric by isolating and correcting the cause of these communication throughput dips in our version of Linux (2.0.29). The availability of this data stream stall metric would provide useful feedback to users by indicating deficient communications performance.